Sistemas petrolíferos especulativos da bacia de Pelotas (offshore do Uruguai) - Paciello, Bruno Conti [UNESP] (2015)
The Pelotas Basin represents an area with potential for hydrocarbons; though still there have not been identified large oil and gas accumulations. A petroleum systems study could contribute to a better characterization and definition of the capacity of the basin to generate and accumulate hydrocarbons. The main purpose of this study is to define the speculative petroleum systems that could be present in the southern portion of the Pelotas Basin to evaluate its hydrocarbon potential. The basin includes a prerift phase that preserved Paleozoic and Mesozoic geological units of the Paraná Basin; an Early Cretaceous volcanic-sedimentary synrift phase and a Cretaceous to Cenozoic postrift controlled by successive transgressions and regressions of the sea level. Sequence stratigraphy was the methodology used to interpret 2D seismic sections, allowing to delimit depositional sequences, system tracts and identifying the distribution of the main elements of the potential petroleum systems. As a result six speculative petroleum systems are proposed. The first system is related to the prerift phase, being represented by a Lower Permian marine source rock and reservoirs related to aeolian and fluvial sandstones of Upper Jurassic age. The second one corresponds to the synrift phase, being constituted by a Barremian lacustrine source rock and presents alluvial and fluvial sandstones of the same age as reservoirs. The third system has as source rock postrift marine shales of aptian-albian age deposited during the first Oceanic Anoxic Event of the Cretaceous (OAE1) and reservoirs represented by Barremian aeolian sandstones related with the Seaward Dipping Reflectors (SDRs). The fourth system has the same Aptian-Albian marine shales as source rock and Upper Cretaceous turbidites as reservoirs. In the fifth proposed system were identified postrift cenomanian-turonian marine shales as source rocks and reservoirs associated with Upper Cretaceous to Cenozoic...